2012
DOI: 10.1007/s00586-012-2296-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multilevel anterior cervical discectomy and fusion versus corpectomy and fusion for multilevel cervical spondylotic myelopathy: a minimum 5-year follow-up study

Abstract: Purpose We evaluated radiologic and clinical outcomes to compare the efficacy of anterior cervical discectomy and fusion (ACDF) and anterior corpectomy and fusion (ACCF) for multilevel cervical spondylotic myelopathy (CSM). Methods A total of 40 patients who underwent ACDF or ACCF for multilevel CSM were divided into two groups. Group A (n = 25) underwent ACDF and group B (n = 15) ACCF. Clinical outcomes (JOA and VAS scores), perioperative parameters (length of hospital stay, blood loss, operation time), radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 19 publications
3
107
1
Order By: Relevance
“…In the past few years, cervical motion preserved through implantation of artificial disc prosthesis has been proved to be an effective and safe alternative option in 1 and 2 level pathologies [10,17,23,39]. However, anterior cervical discectomy and fusion (ACDF) remains the gold standard in the surgical treatment of the patients with multilevel CSM, resulting in well established results and less complications [19,28,36]. The use of stand-alone cage technology in cervical spondylosis was first introduced by Bagby [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, cervical motion preserved through implantation of artificial disc prosthesis has been proved to be an effective and safe alternative option in 1 and 2 level pathologies [10,17,23,39]. However, anterior cervical discectomy and fusion (ACDF) remains the gold standard in the surgical treatment of the patients with multilevel CSM, resulting in well established results and less complications [19,28,36]. The use of stand-alone cage technology in cervical spondylosis was first introduced by Bagby [1].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported on differences between anterior and posterior approaches (n = 9); 15,18,19,22,30,42,44,48,59 laminoplasty and laminectomy and fusion (n = 4); 10,19,70,72 anterior decompression and Bryan disc (n = 1); 11 and anterior cervical discectomy and fusion (ACDF) and corpectomy (n = 2). 47,63 In addition, 11 studies compared laminoplasty techniques or considered technical differences such as laminoplasty with and without foraminotomy or muscle preservation. 28,29,34,38,39,43,57,58,60,66,71 …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Cervical corpectomy represents an alternative technique, which creates a better access to osteophytes behind the vertebral body. Both techniques seem to have similar clinical outcomes and fusion rates when treating two adjacent levels [1]. The number of complications such as cage subsidence, dysphagia, and hoarness of nerve root palsy, increases in double level corpectomies [3].…”
Section: Discussionmentioning
confidence: 97%
“…Multilevel anterior cervical discectomy and fusion represents a current technique in the treatment of spondylotic myelopathy and myeloradiculopathy, if the stenosis remains limited to the level of the disc and the lateral recess [1]. A partial or complete corpectomy and fusion may be preferable in situations where access to the posterior aspect of the vertebral body is needed.…”
Section: Introductionmentioning
confidence: 99%